Zebra Mussel (Dreissena polymorpha) invasion into the Upper Platte River: Using GIS and Genetic Algorithm Rule-set Prediction to model spread - Stimers, Mitchel James (Pennsylvania Geographical Society, 2007)
The introduction of non-native species has been one of the most damaging human impacts on specific ecosystems and the environment in general. Invasive species, such as the Zebra Mussel (Dreisenna polymorpha), are often introduced into an ecosystem inadvertently, but with negative and far-reaching effects on native species. D. polymorpha, since its introduction, has exhibited a devastating propensity for altering the trophic state of lakes and rivers, and has rapidly populated many waterbodies throughout North America. Two rules added to a genetic algorithm rule-set prediction (GARP)model reflect the temporal dimension and the spatial extent of spread. Utilizing GARP, TableCurve, and GIS, I modeled several possible scenarios. Results of the models illustrate the potential for D. polymorpha to continue spreading deeper into the United States as well as the difficulty in predicting the spread of an invasive species.
Keywords: Zebra Mussels; Invasive species; GIS; GARP